2007
DOI: 10.1590/s0004-28032007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori concentration and the combining frequency of histopathological findings in gastric biopsies specimens

Abstract: -Background -Helicobacter pylori is the most prevalent infectious agent worldwide. About 90% of patients with chronic gastritis are infected with this bacterium. Some studies have shown a association between the H. pylori concentration and the scores of gastritis activity and severity. Aim -To evaluate the association between H. pylori concentration and the combining frequency of findings on histopathological examination. Methods -Two hundred consecutive gastric endoscopic biopsies diagnosed as chronic gastrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
5
6
1
Order By: Relevance
“…It has been reported that impairment of gallbladder dynamic functions might be due to inflammation resulting from H pylori infection. In our dyspeptic patients, high incidence of H pylori infection (67%) and delayed GBFT support the hypothesis that this bacteria can cause dyspepsia [2,7,15,16] . On the other hand, since H pylori was found as negative in 33% of our dyspepsia patients, it seemed unlikely that H pylori was the unique factor for dyspepsia.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It has been reported that impairment of gallbladder dynamic functions might be due to inflammation resulting from H pylori infection. In our dyspeptic patients, high incidence of H pylori infection (67%) and delayed GBFT support the hypothesis that this bacteria can cause dyspepsia [2,7,15,16] . On the other hand, since H pylori was found as negative in 33% of our dyspepsia patients, it seemed unlikely that H pylori was the unique factor for dyspepsia.…”
Section: Discussionsupporting
confidence: 86%
“…The H pylori colonizing on the surface of the upper gastrointestinal mucosa is an interesting cause of active chronic gastritis and duodenitis or even gastric cancer worldwide [2][3][4][5][6][7] . The presence of H pylori infection could predispose to various disorders [8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant correlations were detected between HP CagA, inflammation activity grades, and inflammation intensity grades that come in line with others stated that significant correlation was found between HP density and the grade of acute and chronic inflammation [36,37].…”
Section: Al-ezzysupporting
confidence: 89%
“…A significant difference in inflammation activity grades as well as in inflammation intensity grades between CagA positive versus CagA negative APNG patients which come in accordance with others [37,54]. Chronic inflammation due to persistent HP infection expected to cause repetitive degeneration and regeneration of the mucosal epithelium that could facilitate malignant transformation.…”
Section: Al-ezzysupporting
confidence: 85%